2016
DOI: 10.1007/s10266-016-0257-2
|View full text |Cite
|
Sign up to set email alerts
|

Retention strength between veneering resin composites and laser-sintered cobalt–chromium alloy

Abstract: The purpose of the present study was to evaluate the retention strength between a resin composite veneering material and three types of cobalt-chromium (Co-Cr) alloy substrates. Co-Cr alloy specimens with 81 retention devices (LSR), with 144 retention devices (LDR), and without retention device (LN) were fabricated using a laser-sintering system. The specimens were air-abraded with alumina, conditioned with a primer [Alloy primer (AP) or M.L. primer (ML)], and veneered with a light-polymerized resin composite … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This is performed at the stage of the preparation of the wax element, the surface of which is sprinkled with retentive wax beads. After replacing the wax with metal, the obtained retention elements increase the bond strength of the composite to the cobalt chrome alloy as much as two-fold [ 68 ].…”
Section: Establishing Connections Between Composite Systems and Other...mentioning
confidence: 99%
“…This is performed at the stage of the preparation of the wax element, the surface of which is sprinkled with retentive wax beads. After replacing the wax with metal, the obtained retention elements increase the bond strength of the composite to the cobalt chrome alloy as much as two-fold [ 68 ].…”
Section: Establishing Connections Between Composite Systems and Other...mentioning
confidence: 99%
“…Co-Cr frameworks can be veneered with polymethyl methacrylate (PMMA) [ 22 , 31 ], composite resin [ 32 ], or porcelain [ 15 , 23 , 33 , 34 ]. Li et al [ 16 ] indicated that soft-milled Co-Cr had superior strength after repeated porcelain firings when compared with hard-milled or cast Co-Cr.…”
Section: Introductionmentioning
confidence: 99%